2014
DOI: 10.1089/ten.tec.2013.0344
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Cell Co-Migration Occurrences During Cell Aggregation on Fibroin Substrates

Abstract: A quantitative analytical method was proposed for measuring cell co-migration, which was defined as two or more cells migrating together. To accurately identify and quantify this behavior, cell migration on fibroin substrates was analyzed with respect to intercellular distance. Specifically, cell size was characterized by major diameter, and then, based on these measurements and cell center data, a specific threshold distance for defining co-migration was determined after analyzing cell motion using the Vorono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In hanging culture model under gravitational force, MSs gradually settle down towards bottom forming cell-particle aggregates [17]. Inter-cellular distance has a major influence on aggregate formation since larger distance between cells inhibits inter-cellular cross talk [20]. Smaller particles ensure formation of compact clusters as the distance between particles is lower than the threshold distance for cell-cell communication, and cell density on smaller particles surface is also higher.…”
Section: Discussionmentioning
confidence: 99%
“…In hanging culture model under gravitational force, MSs gradually settle down towards bottom forming cell-particle aggregates [17]. Inter-cellular distance has a major influence on aggregate formation since larger distance between cells inhibits inter-cellular cross talk [20]. Smaller particles ensure formation of compact clusters as the distance between particles is lower than the threshold distance for cell-cell communication, and cell density on smaller particles surface is also higher.…”
Section: Discussionmentioning
confidence: 99%
“…This is because, in addition to the high chondrocyte density observed on the bFGF‐fused fibroin sponges [Fig. (A,C)], the distinct adhesion and aggregation formation of chondrocytes observed on fibroin surfaces are considered to affect the chondrogenic phenotype positively . We are currently investigating the use of bFGF‐fused fibroin sponges as a scaffold for cartilage regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Wound dressings must protect and maintain suitably moist environments at the wound site to achieve effective healing throughout normal repair processes. Quantitative analyses of migrations and ECM productions of mouse fibroblasts on the SF surface revealed that fibroblasts on the SF surface migrated more actively and showed higher gene expression of ECM-related proteins than these on the collagen or fibronectin surfaces [12]. In the case of human keratinocytes, cells migrated more actively on the SF surfaces than on the Col surface.…”
Section: Gene Expression On Spongementioning
confidence: 92%
“…Time-lapse microscopic images were taken using a high sensitivity cool CCD color camera (Keyence Co., Tokyo, Japan) for 24 h at 5 min intervals. Migration pathways of WI-38 fibroblasts on surfaces were tracked using MtrackJ software (http://www.imagescience.org/meijering/software/mtrackj/) for quantitative evaluation [12,13].…”
Section: Cell Culture and Migrationmentioning
confidence: 99%
See 1 more Smart Citation